Debit Pemberian Air Irigasi Pada Saluran Irigasi Tersier Di DAS Bluncong Desa Cangkring Kecamatan Prajekan - Wahyudi, Muhammad Nur Zuhudil; Listriyana, Ani; Silviyanti, Nurul Amalia (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2024)
The Bluncong River plays a crucial role in supporting the livelihoods of the local community, especially in the agricultural sector. Research was conducted in Cangkring Village, Prajekan Subdistrict, Bondowoso Regency, from November 2023 to February 2024. The aim of this study is to provide an overview of the advantages and shortcomings of the Bluncong River's water discharge. From the study, data was obtained regarding water discharge deficits at each measurement gate. The lowest water discharge was recorded between November 1-10, 2023, at the 1 Right gate, with a value of 2.03 l/s, while the lowest discharge per hectare was recorded at the 5 Right gate during the same period, amounting to 0.34 l/s/ha. The highest water discharge occurred between January 21-31, 2024, reaching 218.88 l/s, but the highest discharge per hectare was recorded at the 5 Left gate during the same period, with 2.51 l/s/ha. The average water discharge during the planting season was 1.25 l/s/ha, during the maintenance season it was 1.14 l/s/ha, and during the harvest season it was 0.88 l/s/ha